Helper or cytolytic functions can be selectively induced in bifunctional T cell clones (The Rockefeller University Press, 1990)
By using bifunctional T cell populations, we have shown in this report that elicitation of helper versus cytolytic function depends on the stimulatory signal at the membrane. Interestingly enough, the transduction of these signals is likely to be achieved via different metabolic pathways. Thus, helper function is associated with intracellular Ca2+ mobilization and PLC activation, while cytolysis can occur even in the absence of detectable levels of these second messengers. These results indicate that selective activation through the same membrane-transducing molecule may orientate T cell function through qualitatively or quantitatively different second messengers. This would be an important part of immune regulation.